(untitled) (Al-Academy, 2020)
Bilingual slogans are an imperative today in our Arabic region. Since the beginning of history, the regions of the world have become colorful with a wide range of local and international languages, which have sometimes competed, broken up or adapted to the new languages that have replaced them. The contemporary era also shows a new linguistic interface influenced by what the region experienced in the post-colonial era, globalization, new learning requirements and the growing cultural exchange in today’s world " What is the role of the "replacement in shapes" on reinforcing the connecting speech in logo Therefore, bilingual designs have become an inevitable reality as a result of those conditions that afflicted the world, and the results and dimensions that they produce may benefit the nations eager to catch up with the peoples who lead the peoples with the achievements they present that represent their viewpoint of a reality that may lead to theses that may be of help in finding solutions for many Among the problems facing the recipient who is looking for visual cues to walk according to design propositions, so the research was organized in several chapters, the first chapter came to define the research problem that was manifested by the following question:(What is the role of binary designs in enhancing communication discourse in logo design?)With the aim of the research specified in: (Exposing the functional dimensions of bilingual logos designs and what they achieve). The theoretical framework focused on three topics, the first topic touched on: (the concept of the job in design), while the second topic focused on: (bilingual slogan design), and the third topic touched on: (types of bilingual slogans). Then three research models were described and analyzed, based on the analysis paragraphs drawn from the theoretical framework, and the resulting indicators. After that the researcher presented the results and the conclusions reached by the researcher, and from the results:- The need for Iraqi institutions and companies to pay attention to designing bilingual slogans and the slogan in particular to keep pace with the scientific development in the field of design, through the use of academic and specialized designers.Then the search was appended to the list of sources related to the search ... and the research summary is in English.